Ciclesonide exhibits lung-protective effects in neonatal rats exposed to intra-amniotic enterotoxin - Mielgo, Victoria; Gastiasoro, Elena; Catozzi, Chiara; Ricci, Francesca; Gomez-Solaetxe, Miguel A.; Murgia, Xabier; Rey-Santano, Carmen (Frontiers in Pediatrics, 2024)
Introduction: Despite the advances in perinatal care, bronchopulmonary dysplasia (BPD) continues to be a highly prevalent chronic lung disease that affects newborns, especially those born prematurely. There is no specific cure for BPD and treatment to reduce the risk of developing BPD focuses mainly on lung-protective ventilation strategies, and surfactant and/or corticosteroid administration. Our objective was to evaluate whether systemic postnatal administration of a new glucocorticoid, ciclesonide, can attenuate the alteration of lung structure and pulmonary hypertension in a rat model of chorioamnionitis-induced BPD, with minimal adverse effects on the developing brain. Methods: Endotoxin (ETX) or saline was administered to pregnant rats by intra-amniotic (i.a.) injection on day 20 of pregnancy, and pups were delivered by cesarean section on day 22. Ciclesonide (0.5 mg/kg) was administered postnatally for 5 consecutive days to pups previously exposed to i.a. ETX. On postnatal day 14, we assessed lung function (compliance), lung structure (radial alveolar count, mean linear intercept, pulmonary vessel density), pulmonary hypertension and brain histology (edema, inflammation, apoptosis, hemorrhage, and infarction). Result: On postnatal day 14, the effects of i.a. ETX administration were evident in neonatal rats not receiving treatment, these animals showed impaired lung compliance and lung structure and developing pulmonary hypertension compared to results after i.a saline administration. Postnatal administration of ciclesonide for 5 days was associated with significantly better outcomes in terms of lung compliance, alveolarization, lung vascular growth, and pulmonary hypertension, without changes in the brain histological parameters evaluated. Conclusion: Postnatal ciclesonide administration preserved lung function and structure, and prevented pulmonary hypertension in a BPD model based on antenatal i.a. ETX administration, without any adverse effects on the brain in development. These findings suggest that a new glucocorticoid, ciclesonide may provide a novel strategy for the treatment of BPD prevention, but more long-term studies are required.